Amil Zakat Operational Fund In Indonesia - Ridwan, Achmad; Athoillah, Mohamad Anton; Jubaedah, Dedah; Maricar, Hudzaifah Muhammad (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This article aims to identify the use of amil rights funds obtained from the results of collecting zakat for one year to interpret QS. at-Taubah (9): 60 and related hadiths, further linked to KMA No. 606 of 2020 and MUI Fatwa No. 8 of 2011. Researchers used qualitative research methods with a normative juridical approach. Researchers used observation and literature study techniques on several interpretation books and hadiths at the data collection stage. They were then analyzed using interactive analysis models in data reduction, data presentation, and inference and verification. This research concluded that the maximum of amil zakat's rights is one-eighth of the set fund for one year, like the opinions of Mujahid and Syafi'i, then adopted into KMA No. 606 of 2020. As for the MUI Fatwa number 8 of 2011, according to the researcher, it is an ijtihad effort to overcome casualty in several locations managing amil zakat funds